Le contrôle étatique de l’islam en Algérie : un héritage de l’époque coloniale - Stéphane Papi (L’Année du Maghreb)
The control of Islam by the State, exemplified by the creation of an “algerian islamic law” and by a number of exceptions to the principle of separation of Church and State was emblematic of French colonial policy in Algeria. The policy was not challenged after independence. The new Algerian state had no interest in abandoning it and saw it as a way to strengthen the legitimacy that a reference to Islam had given to national claim. As Algeria is now confronted with a phenomenon of individualization of religious practices which challenges the monopoly of official Islamic institutions, will the Algerian government break free from the religious field and put an end to a Gallican and Jacobin tradition dating back to colonization?